Mineral composition and gemological characteristics of the petrified wood of the Ulyanovsk region - D. A. Petrochenkov (Известия высших учебных заведений: Геология и разведка, 2019)
For the first time, the mineral composition and gemological characteristics of the petrified wood from the Ulyanovsk region, of jewelry and ornamental quality, have been studied. The petrified wood is associated with the Lower Cretaceous deposits and consists mainly of calcite (up to 73 mass. %); pyrite, apatite, gypsum are present; dolomite, anhydrite, hematite, pyrolusite, organic matter and X-ray amorphous substance have been fixed. According to the technological and decorative characteristics, the petrified wood of the Ulyanovsk region is a quality jewelry and ornamental material of the florogenic group.